2015
DOI: 10.11604/pamj.2015.22.226.6253
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in urological surgeries: a six years review at Muhimbili National Hospital, Dar es salaam-Tanzania

Abstract: IntroductionAntimicrobial prophylaxis for urologic procedures is a major issue, as potential advantages of antibiotic administration should be carefully weighed against potential side effects, microbial resistance, and health care costs. This study aimed to review a six years trend of antibiotic use in urological surgeries at Muhimbili National Hospital (MNH) being an experience in a typical third world environment.MethodsThis was a six years hospital based descriptive, retrospective study conducted of which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…This is a prolonged antibiotic prophylaxis constituting an unnecessarily excessive antibiotic exposure, which is an important driver of AMR emergence and spread. Similar observations were seen from the hospital in Dar es Salaam regarding use of ceftriaxone for prophylaxis where 86.4% of patients were put on post operative ceftriaxone prophylaxis for up to five days in the majority of elective, clean surgeries[8] and for surgeries involving thyroidectomy (58.2%) and cystectomy (47.8%) [28]. Prolonged surgical ceftriaxone prophylaxes are also observed in a tertiary care hospital in Ethiopia where (94%) had post operative prophylaxis and (70%) used ceftriaxone [29].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…This is a prolonged antibiotic prophylaxis constituting an unnecessarily excessive antibiotic exposure, which is an important driver of AMR emergence and spread. Similar observations were seen from the hospital in Dar es Salaam regarding use of ceftriaxone for prophylaxis where 86.4% of patients were put on post operative ceftriaxone prophylaxis for up to five days in the majority of elective, clean surgeries[8] and for surgeries involving thyroidectomy (58.2%) and cystectomy (47.8%) [28]. Prolonged surgical ceftriaxone prophylaxes are also observed in a tertiary care hospital in Ethiopia where (94%) had post operative prophylaxis and (70%) used ceftriaxone [29].…”
Section: Discussionsupporting
confidence: 64%
“…It has an advantage of a wide coverage of pathogens, easy administration as it is once daily dosing–limiting nursing time needed and a low cost compared to many antibiotics. [21] [22][23] Other studies have as well shown a relatively similar extent of use to the current study; for instance, in a study from a tertiary care hospital in Dar es Salaam where ceftriaxone use as urological surgical prophylaxis was 46.1% [8] and in Nigeria ceftriaxone use for a suspected systemic infection was 42.3% [24] and even higher use in Ethiopia empiric ceftriaxone use was 58% [25] presumptive diagnoses of pneumonia, meningitis and sepsis led to ceftriaxone use in 59.3% [12] and the utilization rate of ceftriaxone was found to be high with a point prevalence of 59% where ceftriaxone was empirically used in 79.5% of cases [5]. Thus, generally, the observed ceftriaxone use in the present study as is in other studies is irrationally high as this drug (and as well, other cephalosporins) should only be used as a life saving drug against confirmed severe infections and not prescribed routinely.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Antimicrobials are overused due to poor adherence to TFDA’s dispensing rules and regulations, poor public health facility antibiotic prescribing, and inappropriate public demand. [ 43 , 44 ]…”
Section: Discussionmentioning
confidence: 99%